The Tobosi Fault: Source of the 2011-2012 Tobosi Earthquake Swarm in Central Costa Rica - Araya, María C. (2015)
The Central Costa Rica Deformed Belt (CCRDB) is an ~100-km broad zone of deformation that marks the boundary between the Caribbean Plate and the Panama Microplate. From December 2011 to February 2012, an earthquake swarm took place in a portion of the CCRDB, near the town of Tobosi, 7 km southwest of the city of Cartago. In this study, data recorded by the National Seismological Network of Costa Rica (RSN: UCR-ICE) is used to relocate the earthquakes and calculate their focal mechanisms. Additionally, the tectonic geomorphology of the region is analyzed. The results show a transtension structure near the town of Tobosi, which comprises at least three faults, named: the Tobosi, Tablon, and Alumbre faults. It was found that the Tobosi fault is an active left-lateral strike-slip fault with a normal component and was the source of the Tobosi earthquake swarm.